Simulation modelling of water-supply network as mechatronic system - Kovar, Jiri; Rucka, Jan; Andrs, Ondrej (2014 16th International Conference on Mechatronics Mechatronika (ME), 2014)
Mechatronics as an interdisciplinary field, which combines knowledge from multiple fields uses a comprehensive approach in the design of any technical object. It combines the requirements and their integration into all subsystems of the technical object. This approach, which is described by the VDI 2006 norm, can generally be used in the suggestion of regulation for the pressure pipe networks.